Kaposi’s Sarcoma-Associated Herpesvirus Subversion of the Anti-Inflammatory Response in Human Skin Cells Reveals Correlates of Latency and Disease Pathogenesis - Judith M. Fontana; Justin G. Mygatt; Katelyn L. Conant; Chris H. Parsons; Johnan A. R. Kaleeba (Journal of Skin Cancer)
KSHV is the etiologic agent for Kaposi’s sarcoma (KS), a neoplasm that manifests most aggressively as multifocal lesions on parts of human skin with a propensity for inflammatory reactivity. However, mechanisms that control evolution of KS from a benign hyperplasia to the histologically complex cutaneous lesion remain unknown. In this study, we found that KSHV induces proteomic and morphological changes in melanocytes and melanoma-derived cell lines, accompanied by deregulation of the endogenous anti-inflammatory responses anchored by the MC1-R/α-MSH signaling axis. We also identified two skin-derived cell lines that displayed differences in ability to support long-term KSHV infection and mapped this dichotomy to differences in (a) NF-κB activation status, (b) processing and expression of KSHV latency-associated nuclear antigen isoforms putatively associated with the viral lytic cycle, and (c) susceptibility to virus-induced changes in expression of key anti-inflammatory response genes that antagonize NF-κB, including MC1-R, POMC, TRP-1, and xCT. Viral subversion of molecules that control the balance between latency and lytic replication represents a novel correlate of KSHV pathogenesis and tropism in skin and underscores the potential benefit of harnessing the endogenous anti-inflammatory processes as a therapeutic option for attenuating cutaneous KS and other proinflammatory outcomes of KSHV infection in high-risk individuals.